Effects of Methylphenidate on Weight Gain and Food Intake in Hypothalamic Obesity - Elfers, Clinton T.; Roth, Christian L. (Frontiers in Endocrinology, 2011)
For patients with a craniopharyngioma (CP), treatment of hypothalamic obesity (HO) and hyperphagia following resection and/or radiotherapy is extremely difficult and few reports have been published on potential drug therapies. Psychomotor stimulant methylphenidate (MPH) has been reported to inhibit food intake. In this paper, we report reduction of body mass index (BMI) and appetite in an adolescent CP patient suffering from HO. We then tested the ability of MPH to attenuate the food intake (FI) and body weight (BW) gain in a rat model consistent with the neuroanatomical and metabolic disturbances commonly observed in obese CP patients. Specifically, we used a novel electrolytically generated combined medial hypothalamic lesion (CMHL) affecting the arcuate nucleus (ARC), ventromedial hypothalamic nucleus (VMN) and dorsomedial hypothalamic nucleus (DMN) to induce hyperphagia, rapid weight gain, and adiposity. Both CMHL and control animals (n=7 per group) were administered either methylphenidate HCl (MPH; 20 mg•kg-1•day-1) or saline for four days in a crossover design experiment 28 weeks post surgery. A significant decrease in percent baseline FI (CMHL -23%, p=0.008; control -20%, p=0.002) and percent change in BW (CMHL -1.97%/4 days, p=0.011; control -1.75%/4 days, p=0.003) was observed during MPH treatment as compared to saline. Conclusion: This study shows MPH treatment of severely obese CMHL rats resulted in significantly reduced FI and BW loss.